2022
DOI: 10.1144/sp521-2021-151
|View full text |Cite
|
Sign up to set email alerts
|

A Late Triassic vegetation record from the Huangshanjie Formation, Junggar Basin, China: possible evidence for the Carnian Pluvial Episode

Abstract: The Carnian Pluvial Episode (CPE; ∼234‒232 million years ago) is characterized by an accelerated hydrological cycle, global warming and a period of elevated biotic turnover. Using spores and pollen, we reconstruct vegetation and climate changes through a Carnian‒Norian (Upper Triassic) interval of the Huangshanjie Formation from the Junggar Basin, China. Four palynofloras were identified, representing distinct vegetation communities. Among these palynofloras, we observed a prominent shift from a conifer-domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 87 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…While the EPME is considered one of the most signi cant extinction events on Earth, before the onset of the event and following the prolonged recovery, the Earth experienced other major carbon cycle perturbations associated with substantial environmental and climatic change, including, but not limited to, Olsen's Extinction (~273 Ma late Cisuralian to early Guadalupian; Brocklehurst et al, 2017;Zhang et al, 2020), the Guadalupian Carbon Isotope Excursion (G-CIE) ending in the Capitanian Extinction Event (~262 Ma; Wang et al, 2004;Isozaki et al, 2007a Wignall and Atkinson, 2020). Records of these events are relatively common from the Northern Hemisphere (e.g., Krull and Retallack, 2000;Wit et al, 2002;Ward et al, 2005;Coney et al, 2007;Hornung et al, 2007;Retallack et al, 2007;Tabor et al, 2007;Retallack and Jahren, 2008;Thomas et al, 2010;Birgenheier et al, 2010;Shen et al, 2013;Mancuso et al, 2020;Lucas, 2017;Peng et al, 2022) but there is a lack of high-resolution records of these events from high-latitude Southern Hemisphere localities. Here we present new evidence of these events from a drill core recovered in Eastern Tasmania, known as Bicheno-5, including high-resolution carbon isotope chemostratigraphy, elemental and sedimentological data (pXRF and hylogging), as well as a palynological assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the EPME is considered one of the most signi cant extinction events on Earth, before the onset of the event and following the prolonged recovery, the Earth experienced other major carbon cycle perturbations associated with substantial environmental and climatic change, including, but not limited to, Olsen's Extinction (~273 Ma late Cisuralian to early Guadalupian; Brocklehurst et al, 2017;Zhang et al, 2020), the Guadalupian Carbon Isotope Excursion (G-CIE) ending in the Capitanian Extinction Event (~262 Ma; Wang et al, 2004;Isozaki et al, 2007a Wignall and Atkinson, 2020). Records of these events are relatively common from the Northern Hemisphere (e.g., Krull and Retallack, 2000;Wit et al, 2002;Ward et al, 2005;Coney et al, 2007;Hornung et al, 2007;Retallack et al, 2007;Tabor et al, 2007;Retallack and Jahren, 2008;Thomas et al, 2010;Birgenheier et al, 2010;Shen et al, 2013;Mancuso et al, 2020;Lucas, 2017;Peng et al, 2022) but there is a lack of high-resolution records of these events from high-latitude Southern Hemisphere localities. Here we present new evidence of these events from a drill core recovered in Eastern Tasmania, known as Bicheno-5, including high-resolution carbon isotope chemostratigraphy, elemental and sedimentological data (pXRF and hylogging), as well as a palynological assessment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the link between the emplacement of the Emeishan LIP, the G-CIE, extinction, and evidence of the global extent of the event is still heavily debated, owing to the lack of chronologically wellconstrained high-resolution carbon isotope records. (Peng et al, 2022), and the extinction of some Triassic crinoid taxa (Simms and Ruffell, 2018). The CPE is also considered a critical event leading to the rise and diversi cation of dinosaurs (Benton et al, 2018;Bernardi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These coals mark the re-commencement of peat accumulation after the global coal gap (Retallack et al, 1996) that followed the collapse of Permian-Triassic terrestrial ecosystems (Retallack et al, 1996;Dal Corso et al, 2020Zhang et al, 2023a; Figure 1). Palynological studies have independently identified increases in hygrophytic plant abundance through the CPE in the boreal realm (Mueller et al, 2016a), the northeastern Tethys region (Mazaheri-Johari et al, 2022), the western Tethys region (Roghi, 2004;Roghi et al, 2010;Mueller et al, 2016b;Baranyi et al, 2019b;Fijałkowska-Mader et al, 2021), and the eastern Tethys region (Lu et al, 2021;Li L. et al, 2022;Peng et al, 2022), collectively indicating that a relatively humid climate prevailed (Figure 1). However, palynological studies from the Denmark Basin (Lindström et al, 2017) and the United Kingdom (Baranyi et al, 2019a) did not show significant floral changes or increased humid climatic conditions during the CPE, showing that the climatic effects varied spatially.…”
Section: Introductionmentioning
confidence: 99%
“…Records of these events are relatively common from the Northern Hemisphere (eg. 27 , 43 50 ) but there is a lack of high-resolution records of these events from high-latitude Southern Hemisphere localities. Here we present new evidence of these events from a drill core recovered in Eastern Tasmania, known as Bicheno-5, including high-resolution carbon isotope chemostratigraphy, elemental and sedimentological data (pXRF and hylogging), as well as a palynological assessment.…”
mentioning
confidence: 99%
“…It is associated with carbon cycle perturbations of up to − 6 ‰ (cf. 24 26 , 31 , 33 36 , 60 ), changes in land biota including a notable global shift from a conifer-dominated forest community to a fern-dominated community suggestive of increased humidity 27 , and the extinction of some Triassic crinoid taxa 61 . The CPE is also considered a critical event leading to the rise and diversification of dinosaurs 59 , 62 .…”
mentioning
confidence: 99%